ANALISIS LEVEL PEMAHAMAN SISWA PADA KONSEP USAHA DAN ENERGI MELALUI PENERAPAN PEMBELAJARAN KONSEPTUAL INTERAKTIF DENGAN PENDEKATAN MULTIREPRESENTASI - Evelina Astra Patriot (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2019)
This study aims to get an overview of the analysis of the level of understanding of students' concepts through the application of interactive conceptual learning with a multi-representation approach to work and energy concept. The research method used in this study was pre-experiment with the research design used was one-group pretest-posttest. The subjects in this study were 35 students of class X MIA 1 at one of the Sumedang Senior High Schools. This study uses a concept understanding test instrument. The results showed an increase in the level of understanding of students after getting the application of learning. The highest percentage at the MSU level of the work and energy concept in the catapult game increased by 61% while the lowest percentage increase at the MSU level was the work and energy concept in the pole jump sports application which was 51%. In general results, almost all students give positive responses to the application of interactive conceptual learning with multi-representation approaches. It can be concluded that, the application of interactive conceptual learning with a multi-representation approach can increase the level of conceptual understanding of work and energy concept.